Metafora konsep alam dalam ungkapan tradisional Bangka: analisis kognitif semantik - Ismaniar, Nurul; Chandra, Oktiva Herry (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
The existence of various traditional expressions from different regions in Bangka Belitung encourages this research to find out how these traditional expressions are formed, especially in the northern region of Bangka. This study examines the use of a natural concept in Bangka traditional expressions using cognitive semantic analysis, namely Kövecses' conceptualization metaphor. Data were obtained from a book of Bangka traditional expressions written by Khaliffitriansyah, Karyani, and Prayoga (2016). This research uses metaphor conceptualization as a theory, so it only uses metaphorical data. Based on the findings, 20 data containing metaphorical forms were found to be classified based on the conceptualization. Bangka traditional expressions contain metaphors formed in the concept of nature as the most used concept, including using plants, animals, and not man-made entities such as stars, stones, and water.